2013
DOI: 10.12983/ijsres-2013-p217-223
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Millimeter Waves with Low Intensity on Peroxidase Total Activity and isoenzyme Composition in Cells of Wheat Seedling Shoots

Abstract: Abstract. In present work the effect of millimeter waves on both peroxidase total activity and isoenzyme spectrum in wheat seedling cells has been investigated. It is followed from obtained data that the influence of millimeter waves with low intensity on germinating seeds and plant extract invokes the changes of peroxidase isoenzyme spectrum of wheat shoots. At multiple effect of external field when seedlings are cultivated by irradiated water isoenzyme composition changes are observed as well. The enhancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Interestingly the living organisms being on any organization level are exposed to the effect of EMI EHF [8][9][10][11]. There exist many works [10,12,13], where the effect of EMI EHF on different parameters of plants, particularly on intensity of both growth and metabolic processes of wheat seedlings during their germination have been investigated. It has been established that EMI EHF affect on nuclear fractions of wheat seedlings changing the value of electrokinetic potential of nuclear membranes, as well as on .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly the living organisms being on any organization level are exposed to the effect of EMI EHF [8][9][10][11]. There exist many works [10,12,13], where the effect of EMI EHF on different parameters of plants, particularly on intensity of both growth and metabolic processes of wheat seedlings during their germination have been investigated. It has been established that EMI EHF affect on nuclear fractions of wheat seedlings changing the value of electrokinetic potential of nuclear membranes, as well as on .…”
Section: Introductionmentioning
confidence: 99%
“…phospholipid content of nuclear subfractions. Earlier it was shown that the value of electrokinetic potential is correlated with genome functional activity [13]. It was also shown that EMI EHF influence on genetic material -DNA in vitro, moreover result in changing of its melting parameters [8].…”
Section: Introductionmentioning
confidence: 99%